2019
DOI: 10.1016/j.cemconcomp.2018.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of behaviour and cracking susceptibility of cementitious systems under restrained conditions through ring tests: A critical review

Abstract: Cracking occurrence due to shrinkage related effects is a widely recognised issue which is frequently evaluated with the shrinkage restraining ring test. This paper provides a state-of-the-art review of the ring test method, which has been used for the last four decades. The last review on such matter was conducted only in early 2000s; however, a significant amount of studies has been conducted since then and considerable advancements or modifications in this testing method have taken place over the last decad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 89 publications
(208 reference statements)
0
15
0
Order By: Relevance
“…This can be explained based on the bond between the fibers and the cementitious materials. As the bond strength between the fibers and the cement paste increases, a simultaneous increase in the overall stiffness of the fiber–cement paste composite will occur [ 38 ]. This creates a restraining effect which results in a reduction of the overall shrinkage.…”
Section: Resultsmentioning
confidence: 99%
“…This can be explained based on the bond between the fibers and the cementitious materials. As the bond strength between the fibers and the cement paste increases, a simultaneous increase in the overall stiffness of the fiber–cement paste composite will occur [ 38 ]. This creates a restraining effect which results in a reduction of the overall shrinkage.…”
Section: Resultsmentioning
confidence: 99%
“…There have been different arrangements for restraining devices developed, viz plate tests, ring tests and longitudinal tests. Plate and ring tests are out of the scope of this review whilst more relevant information can be found in Bentur and Kovler 15 and Kanavaris et al 16 respectively. Longitudinal tests have, generally, been popular as they enable a material characterisation of paste, mortar and, most importantly, concrete, accounting for the processes for autogenous and drying shrinkage, as well as cement hydration.…”
Section: Significance Of Restraining Devices For Time‐dependent Behavmentioning
confidence: 99%
“…The early age shrinkage, heat release and creep of concrete were normally the main concerns of these studies [5,21,22,23]. The evolution of the restrained stress in concrete was also studied, mostly with the ring tests [24,25,26,27,28]. The early age cracking of cement-based materials in the ring tests mainly resulted from the stress caused by the (autogenous and drying) shrinkage.…”
Section: Introductionmentioning
confidence: 99%